Factors influencing participation and engagement in Green Office operation at Faculty of Social Sciences, Srinakharinwirot University - Srikolchan, Anchalee; Monprapussorn, Sathaporn; Sitthi, Asamaporn (Frontiers in Sustainability, 2026)
IntroductionThis study investigates the perceptions, practices, opinions, needs, and participation approaches of faculty members, operational staff, and students concerning factors influencing the implementation of a Green Office at the Faculty of Social Sciences. The objective is to identify stakeholder engagement and drivers affecting the transition toward a sustainable organizational culture. This research supports Sustainable Development Goals (SDGs) 11 and 12 by promoting sustainable institutional practices and responsible consumption.MethodThe sample comprised 18 faculty members, 10 operational staff, and 158 students from the 2023 academic year. Data were collected via structured questionnaires assessing awareness, environmental practices, opinions, needs, and participation in Green Office initiatives. Descriptive statistics and content analysis were employed to analyze the responses.Results and discussionFindings revealed that faculty members and operational staff demonstrated high awareness of Green Office policies and practices but reported limited actual implementation. Students exhibited low awareness across all measures. Proactive environmental behaviors were most evident among faculty and staff, whereas students actively promoted energy-efficient equipment but showed moderate compliance with turning off lights and waste sorting. Faculty and staff perceived the Green Office as a means to reduce resource consumption and enhance the faculty’s image, while students highlighted the importance of green spaces, paper reduction, and the need for additional training. All groups indicated a need for incentives and improved communication to foster participation. In response, the faculty established a dedicated committee, implemented training programs to raise environmental awareness, and ensured consistent communication via meetings and electronic displays to support the Green Office initiatives.